EFEK SAMPING RADIASI SINAR X DAN SINAR GAMMA PADA DAYA TAHAN RONGGA MULUT - Hj. Barunawaty (DiscoverSys Inc., 2002)
The Radiation which usually use in the Medical World is theX-ray radiation and Gamma ray radiation. Both uses forradiodiagnostic and radiotheraphy, have same characteristicbut from difffent well. X-ray source from X-rayequipmentwhichwork of art Human, whereas Gamma raysource from radioac-tive materialswhich to spout accordingspontaneous andnatu-ralcharacteristic. The use of ionizingradiation high dose which to use in radiotherapy possible togive sideeffect at defence oral component and others bodyeels which still healthy.